2011
DOI: 10.1371/journal.pone.0021178
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Healthy Ranges for Serum Alanine Aminotransferase Levels in Adolescence

Abstract: Background & AimsThere is a worldwide epidemic of obesity among adolescents who subsequently are at increased risk for the development of non alcoholic fatty liver disease (NAFLD). The serum alanine aminotransferase (ALT) is the most frequently used test for screening these individuals, but no age and gender-specific upper limits of normal (ULN) based on healthy population data in children are available. The objective of the present study was to define ULN for ALT in healthy children in order to use this as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
51
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 42 publications
7
51
3
2
Order By: Relevance
“…Some studiesindicated this ALT cutoff level as moderate sensitivity for the pediatric age group; it is proposed that lower levels of ALT may be considered for children and adolescents rather than for adults (9-11). The limited studies that established the normal values of liver function tests in the pediatric age group proposed that the liver enzymes levels are different according to age and gender (12-14). …”
Section: Introductionmentioning
confidence: 99%
“…Some studiesindicated this ALT cutoff level as moderate sensitivity for the pediatric age group; it is proposed that lower levels of ALT may be considered for children and adolescents rather than for adults (9-11). The limited studies that established the normal values of liver function tests in the pediatric age group proposed that the liver enzymes levels are different according to age and gender (12-14). …”
Section: Introductionmentioning
confidence: 99%
“…It is also associated with a large amount of heath care cost [4] . NAFLD represents the most frequent chronic liver disease in the general population and is anticipated to become even more prevalent with time, due to the elevating proportion of people of both younger and older age, obesity and diabetes [5][6][7][8][9] . Putting together, NAFLD is emerging as a serious and global health problem which needs to be more precisely and critically addressed.…”
Section: Introductionmentioning
confidence: 99%
“…However, sampling method is more important than sample size for generalizability. Authors claimed that difference in their findings with previous study in Tehran, which has revealed lower limit for upper normal limits for ALT and AST (3), can be due to sampling, which is only from one city and not whole country and this difference may be also due to lower sample size. They have mentioned that the population studied in Tehran was less than one-fourth of the current nationwide study.…”
mentioning
confidence: 68%
“…You should not compare your total sample size with the number of studied people in one province. Their results seems more representative to Tehran due to your mentioned limitations specifically when Poustchi et al (3) have excluded subjects having abnormal values for factors that correlated with ALT in their study. In different parts of the paper (2), authors have expressed that there are linear associations.…”
mentioning
confidence: 95%